Pengaruh Dosis Ekstrak Kunyit (Curcuma domestica Val.) Terhadap Populasi Ektoparasit Pada Ikan Nila (Oreochromis niloticus) - Budiyanti; Wa Ode Safia; Novita Sari (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
This study aims to determine the effect of turmeric extract doses in controlling ectoparasites in tilapia (Oreochromis niloticus). The experimental design used in this study was a completely randomized design (CRD) with four treatments and three replications. The treatment used is without the administration of turmeric extract, 0.5% turmeric extract, 1% turmeric extract, 1.5% turmeric extract. Identification of ectoparasites is to determine the type of ectoparasites present in tilapia (Oreochromis niloticus). The body parts examined were mucus/scales, gills, tail fin, dorsal fin. Identification of ectoparasites was carried out at the Fish Quarantine Station for Quality and Safety Control of Baubau Fishery Products. The data obtained is calculated by the formula of Prevalence and Intensity. As supporting data in this study, observations and measurements of water quality including temperature, pH, dissolved oxygen were carried out in-situ. To test the effect of turmeric extract in inhibiting ectoparasites in tilapia, analysis of variance was used, if it was significantly different then continued with the BNT test (Least Significant Difference) at a 95% confidence level or = 0.05. Based on the results of the study stated that the parasites that attack tilapia (Oreochromis niloticus) there are 9 types of parasites namely Benedenia sp, Oodinium sp, Chilodonella sp, Tricodina sp, Argulus sp, Caligus sp, Vorticella sp, Zootanium sp, Epistylis sp. Based on the results of the Anova test that during the study, the soaking of turmeric extract did not significantly affect the prevalence value but had a significant effect on the intensity of the parasite. The average survival rate ranged from 50.00% - 90.00. The quality of water in the media is in a condition that is quite suitable for the growth and survival of tilapia (Oreochromis niloticus).